2021
DOI: 10.1002/ece3.7489
|View full text |Cite
|
Sign up to set email alerts
|

Negative frequency‐dependent selection maintains shell banding polymorphisms in two marine snails (Littorina fabalis and Littorina saxatilis)

Abstract: The maintenance of such polymorphisms is not trivial as directional natural selection and genetic drift typically tend to erode diversity over time (Lewontin, 1974;Nielsen, 2005). However, in certain conditions both selection and genetic drift can maintain a polymorphism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 60 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…This can result in a negative feedback loop in which predation drives increase of less-susceptible prey, eventually resulting in reduced predator population size (and thus reduced predation pressure), which in turn reverses prey fitness ranks back in favor of prey that are more competitive at low predation pressure [28]. Predators can also maintain polymorphisms among prey through apostatic selection [30,44,45] and across environmental gradients by selecting for different prey alleles in different environmental contexts [46]. While such effects of predation on prey diversity have been investigated in a broad array of organisms, predatory bacteria are understudied in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in a negative feedback loop in which predation drives increase of less-susceptible prey, eventually resulting in reduced predator population size (and thus reduced predation pressure), which in turn reverses prey fitness ranks back in favor of prey that are more competitive at low predation pressure [28]. Predators can also maintain polymorphisms among prey through apostatic selection [30,44,45] and across environmental gradients by selecting for different prey alleles in different environmental contexts [46]. While such effects of predation on prey diversity have been investigated in a broad array of organisms, predatory bacteria are understudied in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of L . fabalis (Estévez et al, 2020 , 2021 ), which did show a reduced change in frequencies over a hypothetical equilibrium frequency in the course of 20 years. However, larger time spans have not yet been analyzed.…”
Section: Patterns Of Diversitymentioning
confidence: 91%
“…Although most research tacitly assumes the equilibrium of genetic drift and migration as null hypothesis, very few attempts have followed this framework in the study of shell color polymorphism. Besides the examples cited above (Estévez et al, 2020 , 2021 ; Johannesson & Butlin, 2017 ), another exception is Cook ( 1992 ), who indirectly tested genetic drift in the mangrove snail Littoraria pallescens by estimating the effective population size ( N e ) either based on molecular markers or color variation. As the level of diversity for both genetic traits could be explained based on correspondingly estimated N e , he concluded that color variation may be a trait as neutral as molecular variation, although he admitted some local exceptions putatively caused by selection (Cook, 1992 ).…”
Section: Evolutionary Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being such a widespread and accessible group, they have been amongst the most intensively studied marine molluscs (Reid 2007;Reid and Williams 2012;González-Wevar et al 2022). They play a significant role in the ecology of intertidal communities and have been widely used as models in microevolutionary studies of natural selection and genetic differentiation (Williams et al 2003;Kess et al 2018;Estevez et al 2021;Bosso et al 2022). In addition, with the advance of molecular tools, the systematics and taxonomy of the family have been updated (Reid and Williams 2004) to give a more accurate classification of species and description of their distributions.…”
Section: Introductionmentioning
confidence: 99%